Static compression of materials - Soh, Yoong Hong (Nanyang Technological University, 2023)
Static Compression is a form of destructive testing that allows us to obtain important mechanical properties which is essential for various other forms of engineering practices. The ASTM E9-19 standards is provides a set of testing guidelines for uniaxial compression testing but there are still some uncertainties in the testing procedures created following this guideline. Therefore, this project aims to further strengthen and verify the the ASTM E9-19 standards by conducting compression tests using different variances that are ambiguous in the ASTM E9-19 standards. The analyzed results will provide future recommendations for more accurate compression testing.